Self-Decoration of PtNi Alloy Nanoparticles on Multiwalled Carbon Nanotubes for Highly Efficient Methanol Electro-Oxidation - Zhou, Yu-Yan; Liu, Chang-Hai; Liu, Jie; Cai, Xin-Lei; Lu, Ying; Zhang, Hui; Sun, Xu-Hui; Wang, Sui-Dong (Nano-Micro Letters, 2016)
A simple one-pot method was developed to prepare PtNi alloy nanoparticles, which can be self-decorated on multiwalled carbon nanotubes in [BMIm][BF4] ionic liquid. The nanohybrids are targeting stable nanocatalysts for fuel cell applications. The sizes of the supported PtNi nanoparticles are uniform and as small as 1–2 nm. Pt-to-Ni ratio was controllable by simply selecting a PtNi alloy target. The alloy nanoparticles with Pt-to-Ni ratio of 1:1 show high catalytic activity and stability for methanol electro-oxidation. The performance is much higher compared with those of both Pt-only nanoparticles and commercial Pt/C catalyst. The electronic structure characterization on the PtNi nanoparticles demonstrates that the electrons are transferred from Ni to Pt, which can suppress the CO poisoning effect.